EFISIENSI PRODUKSI MINYAK MENTAH KELAPA SAWIT DI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR (STUDI KASUS PT. RIAU MAKMUR) - Fakhrunnas, Muhammad; Harahap, Azwar; Iyan, Rita Yani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Development of oil palm plantations in Riau bring major changes to the state of rural communities, especially migrant communities (transmigration), because oil palm development program was originally associated with the transmigration program. In addition, with the development of oil palm plantations also stimulate the growth of the processing industry with raw materials from palm oil. This study aims to determine the effect of capital, labor, and raw materials for production efficiency levels of crude palm oil at PT. Riau Makmur and determine the level of efficiency of crude palm oil production has been achieved by PT. Riau Makmur. The results showed that the factors of production capital and labor are not significantly influence the production of crude palm PT. Riau Makmur. Meanwhile, raw materials production factors were significant effect on the production of crude palm oil PTRiau Makmur.Keywords: Capital, Labor, Raw Materials and The Level of Production Efficiency